Intima-media thickness and arterial function in obese and non-obese children. Issue 1 (December 2015) - Weberruß, Heidi; Pirzer, Raphael; Böhm, Birgit; Dalla Pozza, Robert; Netz, Heinrich; Oberhoffer, Renate
Abstract Background Obesity is an independent cardiovascular risk factor that contributes to the development of atherosclerosis. Subclinical forms of the disease can be assessed via sonographic measurement of carotid intima-media thickness (cIMT) and distensibility – both may already be altered in childhood. As childhood obesity increases to an alarming extent, this study compares vascular data of obese with normal weight boys and girls to investigate the influence of obesity on cIMT and distensibility of the carotid arteries. Methods cIMT and distensibility of 46 obese children (27 girls) aged 7–17 years were compared with measures of 46 sex- and age-matched normal weight controls. cIMT and distensibility were measured by B- and M-mode ultrasound and expressed as standard deviation scores (SDS). Arterial distensibility was defined by arterial compliance (AC), elastic modulus (Ep), stiffness index β (β), and local pulse wave velocity β (PWV β). Results Obese girls had significantly stiffer arteries compared with normal weight girls (Ep SDS 0.64 ± 1.24 vs. 0 ± 1.06, β SDS 0.6 ± 1.17 vs. -0.01 ± 1.06p < .01, PWV β 0.54 ± 1.2 vs. -0.12 ± 1.05p < .05). No significant differences were observed for boys. In multiregression analysis, BMI significantly influenced Ep, β and PWV β but not cIMT and AC. Conclusions Obese girls seemed to be at higher cardiovascular risk than boys, expressed by stiffer arteries in obese girls compared with normal weight girls. Overall, BMI negatively influenced parameters of arterial stiffness (Ep, β and PWV β) but not compliance or cIMT.